(untitled) (BIRDEM Medical Journal, 2021)
Background: Guillain-Barre syndrome (GBS) is an acute, frequently severe and fulminant polyradiculoneuropathy that is autoimmune in nature. Incidence and predominant subtypes of GBS differ geographically. Electrophysiology has important role in subtyping GBS. This study aimed to evaluate the electrophysiological findings in patient of GBS. Methods: This was a hospital based cross-sectional descriptive study and conducted at the Department of Neurology in Sir Salimullah Medical College & Mitford Hospital, Dhaka and National Institute of Neurosciences and Hospital, Dhaka during July 2017 to June 2018. Clinically diagnosed 53 patients with GBS were enrolled according to prefixed selection criteria. Detail history taking, clinical examination, nerve conduction study and cerebrospinal fluid (CSF) examination was performed in all cases. Clinical findings, nerve conduction study (NCS) parameters, CSF findings and demographic profiles were evaluated. Results: Mean ± SD age of presentation was 41.64 (±14.56) years and median age was 42.0 years. There were total 33(62 %) males and 20 (38 %) females with male: female ratio of 1.7:1. Clinically two-thirds(62.3%) of patients had both upper and lower limb involvement (62.3%), facial weakness was in 32.1% and 13.2% had bulbar involvement. Acute inflammatory demyelinating polyneuropathy (AIDP), acute motor axonal neuropathy (AMAN) and acute motor sensory axonal neuropathy (AMSAN)were found to be 51%, 32% and 17% respectively. CSFprotein was elevated in most of the patients with a range of 16-725 mg/dl. Highest CSF protein was found in AIDP. Conclusion: Electrophysiological studies play an important role in the early detection; characterization of GBS.In this study, the commonest type of GBS was AIDP. Higher levels of CSF protein, absent H-reflex and Fresponse, sural sparing and unexcitable nerves are more frequently present in AIDP. BIRDEM Med J 2022; 12(1): 16-21